Effect of plateout, air motion and dust removal on radon decay product concentration in a simulated residence - Rudnick, S N; Hinds, W C; Maher, E F; First, M W (Health physics (1958), 1983)
The effectiveness of increased air motion and dust removal in reducing radon decay product concentration in residences subject to radon intrusion was evaluated in a 78-m3 room under steady-state conditions for air infiltration rates between 0.2 and 0.9 air changes per hour. Room-size, portable electrostatic precipitators and high-efficiency fibrous filters were tested as typical residential air cleaning devices; a portable box fan and a ceiling fan were employed as typical residential air movers. Reductions in working levels of 40-90% were found. The fate of radon decay products, with and without mixing fans, was determined by direct measurement. When mixing fans were used, most of the nonairborne potential alpha-energy was plated out on the room surfaces; less than 10% was deposited on the fan blades or housing. Results were compared to a mathematical model based on well-mixed room air, and good agreement was obtained.